THE PARTICIPATION IN NON-FORMAL EDUCATION ACTIVITIES AND ADAPTATION IN LABOUR MARKET OF ARMENIAN YOUTH (EDUCATION IN THE 21ST CENTURY, 2023)
The main aim of the research is to identify what are the main social adaptation practices of the RA youth in the labor market, to what extent the participation of the youth in non-formal education contributes to the involvement in the labor market. In the post-war and post-pandemic conditions, there are still not many studies on youth employment in Armenia. The level of unemployment among Armenian youth continues to be high in Armenia, and after the pandemic and the war, it has become even worse. Non-formal education can serve as a tool to adapt to the demands of the labor market, as researches document that the connection between education and the labor market in the global world and in Armenia is broken. The analysis of the research results allows us to conclude that informal education serves to get a better job and a higher salary, but does not contribute to entering the labor market. Also, those young people who have professional education and are already involved in the labor market receive informal education. The main part of young people who have received higher education and at the same time informal education have employment, along with the growth of the basic educational level of young people and receiving informal education, the proportion of those with employment increases․
Keywords: Non-formal education in Armenia; education and the labor market; social adaptation of young people; unemployment of young people; employment of young people; youth independence